Mental Health Professionals’ Perspectives on Group Intervention for Women Survivors of Intimate Partner Violence: A Qualitative Study - Chinnadurai Periyasamy; Gitanjali Narayanan; Arun Kandasamy; Sinu Ezhumalai (Journal of Psychiatry Spectrum, 2024)
Background: To examine the perspectives of mental health professionals on providing group intervention for female spouses of men with alcohol dependence who experienced intimate partner violence (IPV). Methods: A qualitative research design was used, and a purposive sample technique was used to select the participants. Nine experts with more than five years of experience in handling partner violence cases provided insights through in-depth interviews. The transcripts were carefully examined several times, coded and re-coded. The codes were subsequently organized into thematic categories. Results: Most of the experts were between the age of 35-45 years (66.7%), females (77.8%) and had more than five years of experience in mental health and IPV (55.6%). Most of the experts (66.7%) were working in teaching institutions related to mental health and IPV. The remaining one-third (33.3%) of the experts were legal and women empowerment practitioners. The thematic analysis generated six main themes and 19 subthemes, with 189 codes. The six mean themes were: psychosocial needs and concerns, psychosocial interventions, enhancing psychological well-being, enhancing the social support systems, challenges, and therapeutic strategies. Conclusion: Experts emphasized the importance of a holistic approach to IPV intervention. Group intervention addresses multiple issues that contribute to violence. Survivors need safe housing, counseling, legal help, and financial assistance.